Plasma Orexin-A Levels Do Not Undergo Circadian Rhythm in Young Healthy Male Subjects - Mäkelä, Kari A.; Karhu, Toni; Jurado Acosta, Alicia; Vakkuri, Olavi; Leppäluoto, Juhani; Herzig, Karl-Heinz (Frontiers in Endocrinology, 2018)
Orexin-A (OXA) has been originally isolated from a precursor peptide prepro-orexin from the lateral hypothalamus. The orexin system has been attributed to important functions in sleep, arousal and regulation of energy homeostasis. In addition to its high levels in cerebrospinal fluid, OXA is present in blood. However, reported peptide concentrations in plasma vary significantly depending on the method used. Therefore, a specific and sensitive OXA radioimmunoassay (RIA) with solid phase extraction method was developed to determine whether plasma OXA concentrations is affected by acute feeding and/or wake and sleep in young healthy males. Blood samples were collected for 24 h from nine healthy males (aged 20–24 years; BMI 20.7–26.5) every 2 h starting at 11 a.m. Food was served at 12 p.m, 5:30 p.m, 8 p.m and 8 a.m and the sleep time was between 10 p.m and 7 a.m. Plasma samples were analyzed in addition for cortisol and melatonin levels. Blood pressure was monitored through the experimental period. OXA antibody was raised in rabbits. OXA antiserum had only minor cross-reactivity with prepro-orexin precursor (<0.001%), amino-terminal peptide (<0.001%), carboxy-terminal peptide (0.001%), and orexin-B (0.3%) with high sensitivity (0.15 pg/tube). Plasma OXA levels varied between 0.5 and 16 pg/ml in seven subjects and were undetectable (below 0.5 pg/ml) in two subjects. The OXA concentrations did not correlate to feeding nor wake/sleep, whereas cortisol, melatonin and mean arterial blood pressure presented a clear circadian rhythm in each subject. In conclusion, OXA is present in blood in low amounts and its levels do not follow autonomic nor neuroendocrine circadian rhythms. Thereby, studies examining regulatory mechanisms and influences of OXA from blood samples should interpret results very cautiously.